(untitled) (Salud, Arte y Cuidado, 2026)
A descriptive cross-sectional study was conducted to assess the nutritional status, frequency of anemia, and food consumption in children aged 2-4 years attending early childhood education centers in the Andrés Eloy Blanco community. The non-probability convenience sample consisted of 104 children aged 2-4 years and their parents or guardians who were surveyed to determine the weekly frequency of food consumption. Preschoolers were weighed and measured, and the data were entered into the WHO Anthro® program. A presumptive nutritional diagnosis was made based on the height/age and weight/height indicators. Finally, venous blood samples were taken and analyzed to obtain hemoglobin values. The data were processed using the SPSS-18 statistical program, resulting in 14.4% with stunting and 12.5% with overweight or obesity. The frequency of anemia was 10.6%, and the frequency of fruit and vegetable consumption was low compared to the recommendations of the food pyramid, with less than 20 times per week (82.7%). Preschoolers identified with malnutrition, anemia, and/or inadequate dietary habits were referred to the pediatric clinic. These results highlight the need to train healthcare professionals to promote healthy eating habits, with the aim of improving the nutritional status of children and the general population in the medium and long term.